Role of Cohesive Discordant Bodies on Fault-And-Thrust Belts Deformation Pattern: An Approach Based on Analogue Modelling [Influencia de Cuerpos Discordantes de Distinta Cohesión en la Geometría Estructural de Fajas Plegadas y Corridas: Aproximación Sobre la Base de Un Modelamiento Analógico] - Jara-Munoz, P (Servicio Nacional de Geologia y Mineria, 2021)
Role of cohesive discordant bodies on fault-and-thrust belts deformation pattern: an approach based on analogue modelling. Lithological heterogeneities in a rock series deformed by the development of a fold-and-thrust belt (FTB) affects the pattern of the resulting structures. We present a series of analogue experiments to determine the effect caused on the deformation pattern of a FTB by the presence of cohesive bodies, like plutons or basement blocks that oppose greater resistance than the host rocks to contractional deformation. The influence of these bodies on the deformation pattern of the FTB was studied by incorporating discordant bodies with different cohesions within a stratified granular sequence with negligible cohesion. We describe two sets of experiments in which the inserted body presents low (Co1) and high (Co2) cohesion respectively. The experiments show a tendency of the structural pattern to curve around the inserted body and to migrate towards the deformation front or the foreland, even when the cohesive body is not exposed. In the first case (Co1) the thrusts cut across the cohesive body, while in the second one (Co2) the cohesive body is not faulted, but transferred towards the deformation front along a basal detachment. Comparison of these results with natural examples at different scales shows a high degree of coincidence in the structural patterns recognized in both cases. Two of the main characteristics of these patterns are the tendency of the thrust faults traces to avoid the cohesive body and adopt the geometry of its distal edge. In order to explain curvatures in natural structural patterns in fold-and-thrust belts, we suggest consider the presence of unexposed bodies with higher strength than their environment. © 2021, Servicio Nacional de Geologia y Mineria. All rights reserved.